Blow up of Solutions for the Logarithmic Higher-Order Kirchhoff-Type Equation with Variable Exponent - Yılmaz, Nebi; Pi¸skin, Erhan (Journal of Nepal Mathematical Society, 2024)
In this work, we investigate the logarithmic higher-order Kirchhoff-type equation with variable exponents as follows (Equation can be seen in the article). We proved that under suitable conditions on the initial data, a finite-time blow up result for solutions with negative initial energy.